Richard Rorty or the fear to Enlightenment - Bermudo, José Manuel (Estudios de Filosofía, 1996)
This is a critique of the philosophical view of Rorty on polítical and social problems that reveals its paradoxes and conclude that the provocation and appealing ideas turns his philosophy into an ideology justifying politics in liberal society, namely in the United States of America. The crisis of Modernity is a fact a crisis of the reason of the Enlightenment. The author differs on the philosophical posilion usually thought to carry out that crisis, because for him a philosopher believes in knowledge and besides, being the raison d’être of philosophy its compromise with emancipation and libertation of public erudition, it should not be made a matter of one ’s own.